Mitochondrial Asncmtrna-1 and Asncmtrna-2 as Potent Targets to Inhibit Tumor Growth and Metastasis in the Renca Murine Renal Adenocarcinoma Model - Borgna-Christie, V (Impact Journals LLC, 2017)
Knockdown of antisense noncoding mitochondrial RNAs (ASncmtRNAs) induces apoptosis in several human and mouse tumor cell lines, but not normal cells, suggesting this approach for a selective therapy against different types of cancer. Here we show that in vitro knockdown of murine ASncmtRNAs induces apoptotic death of mouse renal adenocarcinoma RenCa cells, but not normal murine kidney epithelial cells. In a syngeneic subcutaneous RenCa model, treatment delayed and even reversed tumor growth. Since the subcutaneous model does not reflect the natural microenviroment of renal cancer, we used an orthotopic model of RenCa cells inoculated under the renal capsule. These studies showed inhibition of tumor growth and metastasis. Direct metastasis assessment by tail vein injection of RenCa cells also showed a drastic reduction in lung metastatic nodules. In vivo treatment reduces survivin, N-cadherin and P-cadherin levels, providing a molecular basis for metastasis inhibition. In consequence, the treatment significantly enhanced mouse survival in these models. Our results suggest that the ASncmtRNAs could be potent and selective targets for therapy against human renal cell carcinoma. © Borgna et al.